TINJAUAN TENTANG IMPLEMENTASI PROGRAM GISA (GERAKAN INDONESIA SADAR ADMINISTRASI KEPENDUDUKAN) PADA KANTOR DINAS KEPENDUDUKAN, PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK (DKP3A)PROVINSI KALIMANTAN TIMUR - Ayu Febryanti Darmawan (ADMINISTRASI PUBLIK, 2020)
Ayu Febryanti Darmawan NPM 16.11.1001.3509.063. Review of the Implementation of the GISA Program (Movement of Indonesia Conscious Population Administration) At the Office of the DKP3A of East Kalimantan Province, this study aims to review the implementation of the GISA program at the Department of Population, Women's Empowerment and Child Protection of East Kalimantan Province. This research is a descriptive study using a qualitative approach. Data collection techniques are done by observation, interview, and documentation.    The informants in this study were the Head of Section for Population Registration Apparatus Development at the Population, Women's Empowerment and Child Protection Department of East Kalimantan Province as the main informant, as well as 5 community recipients of the GISA program. Data analysis techniques used are divided into several stages, namely data collection, data condensation, data presentation, and drawing conclusions. While checking the validity of the data is done by triangulating sources.    This study reviewed the implementation of the GISA program in the Department of Population, Women's Empowerment and Child Protection in East Kalimantan Province assessed from the dimension of being aware of the importance of population documents, being aware of population data utilization, being aware of updating population data, being aware of the importance of population administration that makes people happy. Based on (1) the conscious dimension of the importance of population documents, the level of public awareness has begun to increase considering population documents are very important to facilitate all matters of affairs, (2) the conscious dimension of population data utilization, utilization of population data is needed to facilitate matters and now the public easily uses , (3) the conscious dimension of data updating, the updating of data is still being improved for the convenience of the public and the government to collect data to prevent duplicate data, by continuing to socialize data updating so that data differences do not occur in the field, (4) the conscious dimension to the importance of happy population administration the people, the government keeps trying to do well to make things easier to take care of documents and improve services.